Pengaruh Kerapatan Pohon dan Pemupukan Nitrogen terhadap Pertumbuhan dan Produktivitas Rumput di Bawah Tegakan Samama (Anthocephalus macrophyllus (Roxb. Havil.) - Sri Handayani; Irdika Mansur; Panca Dewi Manohara Karti (Jurnal Silvikultur Tropika, 2019)
Samama (Anthocephalus marcophyllus Roxb.Havil) is a tree with a canopy like a large umbrella so that if planted at any distance it will not affect the shape of the stem (Halawane et al. 2011). This type can flourish in tropical forests with an altitude of 50-1000 mdpl. This is including native Indonesian plants that have the potential to be developed in the development of plantation forests and for other purposes, such as reclamation of ex-mining land, reforestation and shade trees (Mansur and Tuheteru 2010). This is because samama can grow on various types of soil, do not have serious pests and diseases (Pratiwi 2003). In accordance with the permit for the implementation of silvopatura activities in production forest areas which are explained in full in the regulations of the Ministery of Environment and Forestry of the Republic of Indonesia No. P.14/Menlhk-11/2015 concerning procedures for granting business licenses for the utilization of silvopastura areas in production forests with the aim of ensuring sustainable forest management by applying the principles of good governance. In the framework of sustainable production forest management to support food sovereignty programs. Provision of sufficient light space, fertilize and selection of tolerant grass species under stands are the key to the success of silvopastura. Based on the results of the study, it was found that the density of trees with 2 tree/plot with light intensity in the morning was 70.48% and 95.29% during the day. Addition of nitrogen to grass is not needed if the soil used has good fertility. Pennisetum purpureum Cv. Mott has the best tolerance under the same stand as a source of cut grass (intensive retention) and Stenotaphrum secundatum a coarse, hardly perennial grass in the management of silvopastura extensive. Key words: silvopasture, density of tree, shade, samama